Kăyănupassană : kăya, vedană, citta nhaṅʻ' dhammănupassană satipaṭṭhānʻ 4 pă" luṃ" pra chui thă" saññʻ - Paṇḍita, ʼA rhaṅʻ, 1893- (Haṃsăvatĭ că ʼupʻ tuikʻ, 1977)
On Buddhist meditation contemplating the ephemeral nature of the human body.